Improvement of the Performance of Graphite Felt Electrodes for Vanadium-Redox-Flow-Batteries by Plasma Treatment - Hammer, Eva-Maria; Berger, Benedikt; Komsiyska, Lidiya (Center of Biomass & Renewable Energy, Diponegoro University, 2014)
In the frame of the present contribution oxidizing plasma pretreatment is used for the improvement of the electrocatalytic activity of graphite felt electrodes for Vanadium-Redox-Flow-Batteries (VRB). The influence of the working gas media on the catalytic activity and the surface morphology is demonstrated. The electrocatalytical properties of the graphite felt electrodes were examined by cyclic voltammetry and electrochemical impedance spectroscopy. The obtained results show that a significant improvement of the redox reaction kinetics can be achieved for all plasma modified samples using different working gasses (Ar, N2 and compressed air) in an oxidizing environment. Nitrogen plasma treatment leads to the highest catalytical activities at the same operational conditions. Through a variation of the nitrogen plasma treatment duration a maximum performance at about 14 min cm-2was observed, which is also represented by a minimum of 90 Î© in the charge transfer resistance obtained by EIS measurements. The morphology changes of the graphitized surface were followed using SEM.